ANALISIS PERBANDINGAN TOLERANSI KESALAHAN (FAULT TOLERANCE) ROUTING STATIC DAN OSPF PADA JARINGAN HYBRID UNUD - Anugrah Br. Ginting, Putri; Diafari, G A K; Indra ER, Ngurah; Wiharta, Dewa Made (Jurnal SPEKTRUM, 2024)
A reliable and failure-resistant computer network is an important prerequisite in the modern interconnected environment. This research aims to examine and compare the effectiveness of fault tolerance between two commonly used routing protocols, namely static routing and OSPF (Open Shortest Path First), in the context of hybrid networks at Udayana University (UNUD). This research uses GNS3 to simulate the UNUD network environment. The research method is carried out by implementing static and OSPF routing separately in the GNS3 simulation. After the routing implementation is carried out, the network is tested against various error scenarios to observe how each routing method handles the situation.In this research, the analysis results provide a deeper understanding of the advantages and disadvantages of each routing method. Our findings illustrate that OSPF significantly improves fault tolerance and network availability compared to static routing in complex hybrid network environments.